Non-Timber Forest Products Used as Commercialized Crafts in Padang Panjang City West Sumatra - Desmayanti, Resti; Kardiman, Reki; Anhar, Azwir; Violita, Violita (Jurnal Biologi Tropis, 2024)
Non-Timber Forest Products (NTFPs) are a part of forest ecosystem which have various roles, both in the natural environment and in human life. The NTFPs usually used as the basis for alternative economic value of a forest, and the demand for NTFPs are related to forest management. Plants are often  used as NTFPs, and the highest demand of the products is handicraft that are bought and sold across economic centers, but the detail information about the NTFPs and their derivative products in those capital areas are less known. This research investigates the use of NTFPs for craft products in Padang Panjang City, West Sumatra, Data on plant species, the derivate craft products, the part of plant used, sizes, water content, the demand for raw material for each product, place of origin, and the prices were colleted directly to all three existing craft shops in Padang Panjang City. Four plant species were found for making 17 types of craft products, namely bamboo (Bambusa spp.), rattan (Calamus spp.), coconut (Cocos nucifera L.), and pandan (Pandanus spp.). The most craft products was made from rattan, and the most part of plants used was the stem, which less than 30 mm in size, and below 14% in water content. Coconut and Pandan was found as fruit and leaves. Only two of 17 products were made locally in Padang Panjang.  The results of this research show that rattan as a type of NTFPs that mostly commercialized for craft products in Padang Panjang City. This data can be used for communities living at forest adjacent around Padang Panjang City on extracting the NTFPs.